Analysis of the Effect of Management Control Systems on Employee Performance Moderated by Transformational Leadership at Dr. RM. Djoelham Regional General Hospital in Binjai City - Ermina BR. Sitepu; Mesra B (Lafadz Jaya Publisher, 2023)
The aim of this research is to analyze and investigate the influence of management control systems on employee performance which is moderated by transformational leadership at Dr. RM. Djoelham, Binjai City. This type of research is associative quantitative. The location of the research was carried out at Dr. General Hospital. RM. Djoelham City of Binjaii. The population in this study is the total number of employees as many as 357 employees. The sampling technique used was random sampling using the Slovin formula and a sample size of 78 employees was obtained. The data collection technique used is by distributing questionnaires. Data analysis in this study used Smart PLS 3.0 with the Moderated Regression Analysis (MRA) test model. The results of this research show that the management control system has a significant effect on employee performance at the Dr. Regional General Hospital. RM. Djoelham, Binjai City with a P-Value of 0.000 < 0.05. This means that if the management control system is improved, employee performance at Dr. Regional General Hospital will improve. RM. Djoelham Binjai City will also increase. In the Moderated Regression Analysis (MRA) test, a T-Statistic value of 0.332 > 1.96 is obtained with a P-Value of 0.741 > 0.05, which means that the moderating variable, namely transformational leadership, is not able to significantly strengthen the influence of the management control system on employee performance at home. Regional General Hospital Dr. RM. Djoelham Kota Binjai in other words that the hypothesis is rejected.